All-solid-state quantum dot-sensitized solar cell from plastic crystal electrolyte. Issue 42 (9th April 2015) - Duan, Jialong; Tang, Qunwei; He, Benlin; Chen, Haiyan
Abstract : A plastic crystal based solid-state electrolyte composing of plastic crystal succinonitrile and sodium sulfide (Na2 S) is creatively synthesized by a simple blending approach. Abstract : A plastic crystal based solid-state electrolyte composing of plastic crystal succinonitrile and sodium sulfide (Na2 S) is creatively synthesized by a simple blending approach. The ionic conductivity, charge-transfer ability, and photovoltaic performance are optimized by adjusting the succinonitrile/Na2 S ratio. An optimal power conversion efficiency of 1.29% is measured for its quantum dot-sensitized solar cell (QDSSC) under one sun irradiation. The impressive efficiency along with the simple preparation of the cost-effective Na2 S integrated succinonitrile electrolytes highlights the potential application of plastic crystal electrolytes in solid-state QDSSCs.